John Steinbeck - Bloom, Harold (New York : Chelsea House Publishers, 1987)
A selection of criticism, arranged in chronological order of publcation, devoted to the fiction of John Steinbeck.
Includes index.
Bibliography: p. 161-163.
Keywords: Steinbeck, John, -- 1902-1968 -- Criticism and interpretation